Perancangan dan Implementasi Perencanaan Bisnis dan Strategi Promosi bagi Kelompok Rintisan Usaha Mandiri Sanggar Batik Jenggolo dan Sekar Arum di Kota Yogyakarta - Karina Rima Melati (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2017)
This Community Service program is funded by DIPA scheme of RISET DIKTI No. DIPA-042.06-0.1.401516/2016, which implicated two entrepreneurship groups of empowering woman: Sanggar Jenggolo in Pandean District who produce batik and Sekar Arum (then called ‘Code Arum’) in Cokrodiningratan district who produce jumputan or tie-dye, both in Yogyakarta city. The two groups had been incubated and assisted by The Office for Women and Society Empowerment (Kantor Pemberdayaan Perempuan dan Masyarakat—abbreviated as KPMP) of Yogyakarta Municipal Government for three years. After the accompaniment they face declining of production since it does not fulfill with the business and promotion assistance. Therefore this Community Service program aims to encourage the sustainability of the group with the creation of a Business Plan and Strategy of Promotion to penetrate the target market. We were conducting the training, providing with supporting tools based digital, and producing attributes for their promotion. Furthermore there were outcomes achieved; (A) the core of a Business Plan so that each groups has a priority of their business as well as a guideline for evaluating the development of its business during period of Business Plan. (B) The attributes of corporate identity is implemented through a variety of promotion sale.